The Moderating Effect of Gender on the Relationship Between Intellectual Capital and Audit Quality - Peprah, Williams Kwasi (Advances in Social Sciences Research Journal, 2019)
In our globe today, the auditing profession is under scrutiny. This is because of how audit quality can be ensured, obtained, and maintained. The problem of audit quality is discussed from the viewpoint of intellectual capital and the interaction of the gender of the auditor. Audit quality consists of auditors’ competence and independent, while intellectual capital is made up of human capital, rational capital, and structural capital. This research was a correlational design which applied self-constructed questionnaires with Cronbach alpha of 0.82 and 0.75 for intellectual capital and audit quality respectively. Using a convenience sampling technique, 354(8%) out of 4,390 registered chartered accountants with Chartered Institute of Accountants, Ghana (ICA, GH) who were practicing auditors were used in this study. The study respondents were made up of 191 (54%) males and 163 females, of which 210 (59.3%) had attained degrees, and 144 (40.7%) had an MBA. The study used PROCESS v3.2 and Andrew Haye model 1 to establish the regression and the moderating effect. The results of the study disclosed that there is a high positive significant relationship between intellectual capital and audit quality, and intellectual capital can predict audit quality by 53.68%. Also, there is an enhancing moderating effect of gender on the relationship between intellectual capital and audit quality but not statistically significant. The study recommends that the role of the auditor on audit quality and their intellectual capital must not be differentiated. Therefore, attention must not be placed on the gender of the auditor to give a quality audit.